2021
DOI: 10.1021/acsaem.1c02235
|View full text |Cite
|
Sign up to set email alerts
|

Binary Additive Engineering Enables Efficient Perovskite Solar Cells via Spray-Coating in Air

Abstract: Spray-coating as a high throughput and low-cost deposition process endows perovskite solar cell (PSC) devices the possibility of large-scale production, while the low device efficiency due to poor and uncontrolled film quality impedes the commercialization process of PSCs. Herein, we demonstrate a binary additive engineering strategy to achieve a device efficiency of 18.2% with minor hysteresis by spray-coating the (FAPbI 3 ) x (MAPbBr 3 ) 1−x hybrid perovskite in air. The spray-coated perovskite films have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…[147] Using the same substrate heating and gas quenching method, Fievez et al reported the slot-die coating of methyl ammoniumfree Cs 0.16 FA 0.84 Pb(I 0.88 Br 0.12 ) 3 perovskite film for the fabrication of n-i-p structured PSCs which delivered a PCE of 18% over 0.09 cm 2 active-area device. [149] Moreover, optimization of print- [159] Copyright 2021, American Chemical Society. c) J-V curves of the fully spray-coated PSCs (ITO glass/SnO 2 /perovskite/spiro-OMeTAD/Ag).…”
Section: Slot-die Coatingmentioning
confidence: 99%
See 3 more Smart Citations
“…[147] Using the same substrate heating and gas quenching method, Fievez et al reported the slot-die coating of methyl ammoniumfree Cs 0.16 FA 0.84 Pb(I 0.88 Br 0.12 ) 3 perovskite film for the fabrication of n-i-p structured PSCs which delivered a PCE of 18% over 0.09 cm 2 active-area device. [149] Moreover, optimization of print- [159] Copyright 2021, American Chemical Society. c) J-V curves of the fully spray-coated PSCs (ITO glass/SnO 2 /perovskite/spiro-OMeTAD/Ag).…”
Section: Slot-die Coatingmentioning
confidence: 99%
“…Reproduced with permission. [ 159 ] Copyright 2021, American Chemical Society. c) J–V curves of the fully spray‐coated PSCs (ITO glass/SnO 2 /perovskite/spiro‐OMeTAD/Ag).…”
Section: Printing Techniques For Pscsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 70 ] However, to trigger nucleation during or after spray coating, researchers have also used an antisolvent bath method, [ 29,71 ] although the scalability of this processes is limited by the use of significant quantities of solvent that becomes gradually “contaminated” during any device run. Alternative approaches to induce supersaturation include thermal annealing, [ 72 ] vacuum‐assisted solution processing, [ 73 ] hot‐air blowing, [ 74 ] and plasma‐treatments. [ 22 ] Here, we investigate a GASP protocol in which an ambient temperature nitrogen gas‐jet from an air‐knife is blown at a surface that has been spray‐cast with a perovskite precursor solution, with the evaporation of the volatile casting‐solvent inducing supersaturation.…”
Section: Resultsmentioning
confidence: 99%